Typologie des lacs polaires - Touchart, Laurent (Norois, 2005)
The major typological criterion for classifying polar lakes is the isolation by the ice cover. The significance of this phenomenon depends on the inter-annual regularity of the ice regime. Continental glaciers are the main obstacle between water and atmosphere; perennially frozen lakes are largely isolated too. The seasonally frozen lakes are either shallow and deep lakes. Polar ponds and shallow lakes, which may completely freeze and disappear each year, are biologically poor, whereas deep polar lakes present a complete trophic cycle despite the great water level fluctuations. Le critère typologique de l’isolement dû à la glace est majeur et son importance est replacée en fonction de la régularité interannuelle du taux de la couverture glaciaire ou glacielle. La barrière la plus hermétique est celle d’un glacier continental, suivie par celle d’une banquise lacustre permanente. Chez les lacs à couverture glacielle saisonnière, les plans d’eau superficiels, que le gel est susceptible de faire disparaître chaque année, ont une chaîne trophique beaucoup plus pauvre que les grands lacs profonds, capables de fournir des conditions favorables à la vie malgré l’ampleur du marnage.